Structural and functional analysis of the carotenoid biosynthesis genes of a Pseudomonas strain isolated from the excrement of Autumn Darter. Issue 6 (3rd June 2018) - Fukaya, Yuki; Takemura, Miho; Koyanagi, Takashi; Maoka, Takashi; Shindo, Kazutoshi; Misawa, Norihiko
Abstract: There are many reports about carotenoid-producing bacteria and carotenoid biosynthesis genes. In databases for Pseudomonas genome sequences, there are genes homologous to carotenoid biosynthesis genes, but the function of these genes in Pseudomonas has not been elucidated. In this study, we cloned the carotenoid biosynthesis genes from a Pseudomonas sp. strain, named Akiakane, which was isolated from the excrement of the Autumn Darter dragonfly. Using an Escherichia coli functional expression system, we confirmed that the idi, crtE, crtB, crtI, and crtY gene products of the Akiakane strain show predictable catalytic activities. A cluster of six genes was also found, which was comparable to other carotenoid-producing bacteria that belong to the α-Proteobacteria or γ-Proteobacteria class. Abstract: : The carotenoid biosynthesis genes of a Pseudomonas sp. atrain Akiakane isolated from the excrement of the Autumn Darter, were isolated and analyzed.